Cisplatin + docetaxel improves survival over cisplatin + mitomycin C in hyperthermic intraperitoneal chemotherapy for pseudomyxoma peritonei: a retrospective study based on propensity score matching - Yu-Bin Fu; Rui Yang; Yan-Dong Su; Ru Ma; Tian Wei; Yang Yu; Bing Li; Yan Li (International Journal of Hyperthermia)
Objective Pseudomyxoma peritoneum (PMP) of appendiceal origin poses significant treatment challenges with hyperthermic intraperitoneal chemotherapy (HIPEC) regimens offering viable outcomes. This study aimed to compare the efficacy and safety profiles of two HIPEC regimens: cisplatin + docetaxel (CD) and cisplatin + mitomycin C (CM).Methods PMP patients who underwent cytoreductive surgery (CRS) and HIPEC between January 2008 and December 2023 at our center were retrospectively analyzed. Patients were divided into CD and CM groups and matched for baseline characteristics using propensity score matching (PSM). Clinicopathological data, efficacy, and safety profiles were compared. Univariate and multivariate analyses identified independent prognostic factors, and subgroup analyses further compared the two regimens.Results After PSM, 104 patients met the inclusion criteria (52 in each group). The median overall survival (mOS) was significantly longer in the CD group (156.3 vs. 60.9 months, p = 0.018), with no significant differences in adverse event severity between groups. Multivariate analysis identified HIPEC regimen, completeness of cytoreduction (CC), and pathological type as independent prognostic factors. Subgroup analysis showed significant mOS benefit for the CD regimen in patients with peritoneal carcinomatosis index (PCI) ≥ 27, CC 2/3, high grade pathology, tumor markers ≥1 evaluated and BMI < 25 (all p < 0.005).Conclusions Following CRS, the CD regimen offers superior survival benefits compared to the CM regimen for PMP patients. These findings highlight the potential of personalized HIPEC strategies to optimize outcomes for PMP treatment.